Novel mutations in genes of the IL-12/IFN-γ axis cause susceptibility to tuberculosis - Sajjad Ahmad; Jawad Ahmed; Eman H. Khalifa; Farhad Ali Khattak; Anwar Sheed khan; Syed Umar Farooq; Sannaa M.A. Osman; Magdi M. Salih; Nadeem Ullah; Taj Ali Khan (Elsevier, 2023)
Background: The IL-12/23/ISG15-IFN-γ pathway is the main immunological pathway for controlling intra-macrophagic microorganisms such as Mycobacteria, Salmonella, and Leishmania spp. Consequently, upon mutations in genes of the IL-12/23/ISG15-IFN-γ pathway cause increased susceptibility to intra-macrophagic pathogens, particularly to Mycobacteria. Therefore, the purpose of this study was to characterize the mutations in genes of the IL-12/23/ISG15-IFN-γ pathway in severe tuberculosis (TB) patients. Methods: Clinically suspected TB was initially confirmed in four patients (P) (P1, P2, P3, and P4) using the GeneXpert MTB/RIF and culturing techniques. The patients' Peripheral blood mononuclear cells (PBMCs) were then subjected to ELISA to measure Interleukin 12 (IL-12) and interferon gamma (IFN-γ). Flow cytometry was used to detect the surface expressions of IFN-γR1 and IFN-γR2 as well as IL-12Rβ1and IL-12Rβ2 on monocytes and T lymphocytes, respectively.The phosphorylation of signal transducer and activator of transcription 1(STAT1) on monocytes and STAT4 on T lymphocytes were also detected by flow cytometry. Sanger sequencing was used to identify mutations in the IL-12Rβ1, STAT1, NEMO, and CYBB genes. Results: P1's PBMCs exhibited reduced IFN-γ production, while P2's and P3's PBMCs exhibited impaired IL-12 induction. Low IL-12Rβ1 surface expression and reduced STAT4 phosphorylation were demonstrated by P1's T lymphocytes, while impaired STAT1 phosphorylation was detected in P2's monocytes. The impaired IκB-α degradation and abolished H2O2 production in monocytes and neutrophils of P3 and P4 were observed, respectively. Sanger sequencing revealed novel nonsense homozygous mutation: c.191 G>A/p.W64 * in exon 3 of the IL-12Rβ1 gene in P1, novel missense homozygous mutation: c.107 A>T/p.Q36L in exon 3 of the STAT1 gene in P2, missense hemizygous mutation:: c.950 A>C/p.Q317P in exon 8 of the NEMO gene in P3, and nonsense hemizygous mutation: c.868 C>T/p.R290X in exon 8 of CYBB gene in P4. Conclusion: Our findings broaden the clinical and genetic spectra associated with IL-12/23/ISG15-IFN-γ axis anomalies. Additionally, our data suggest that TB patients in Pakistan should be investigated for potential genetic defects due to high prevalence of parental consanguinity and increased incidence of TB in the country.